2005
DOI: 10.1158/1055-9965.epi-05-0149
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Pathway Polymorphisms Associated with Body Size in Hispanic and Non-Hispanic White Women

Abstract: Polymorphisms affecting insulin-like growth factors (IGF), their binding proteins (IGFBP), insulin receptor substrates (IRS), and other IGF regulatory molecules may affect growth, obesity, and obesity-related diseases, including cancer. The objective of this study was to better describe the associations between several IGF pathway variants and body size. Hispanic (n = 462) and non-Hispanic White (n = 1,702) women were recruited as controls in collaborative population-based case-control studies in Arizona, New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
1
8

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 69 publications
5
16
1
8
Order By: Relevance
“…For the V89L polymorphism, 52% and 44% of NHW and HW controls, respectively, had the VV genotype (P = 0.001). The genotype distributions in controls for these polymorphisms do not differ significantly from previously published results (31,32). Additionally, CDX2 genotype distributions in NHW controls are similar to what was found earlier (33).…”
Section: Resultssupporting
confidence: 82%
“…For the V89L polymorphism, 52% and 44% of NHW and HW controls, respectively, had the VV genotype (P = 0.001). The genotype distributions in controls for these polymorphisms do not differ significantly from previously published results (31,32). Additionally, CDX2 genotype distributions in NHW controls are similar to what was found earlier (33).…”
Section: Resultssupporting
confidence: 82%
“…Consistent with our findings, several studies examining female White Caucasian populations did not find an association between 5¢CA-19 and height [22][23][24] or BMI, 22,25 or between 5¢CA-20 and height. 23 No association between 5¢CA-19 and BMI was found for Hispanic or Chinese women (although among Chinese women 5¢CA-17 was associated with lower BMI).…”
supporting
confidence: 92%
“…23 No association between 5¢CA-19 and BMI was found for Hispanic or Chinese women (although among Chinese women 5¢CA-17 was associated with lower BMI). 25,26 In a study from the Netherlands (Rotterdam), women homozygous for either 5¢CA-19 or 5¢CA-20 were significantly heavier than other homozygotes. 23 Another Netherlands (Amsterdam) study found that homozygous carriers of 5¢CA-19, 5¢CA-20 or 5¢CA-19/20 heterozygotes had significantly higher BMI than women with other genotypes, for one of two cohorts examined.…”
mentioning
confidence: 98%
“…36 Numerous conflicting studies show no evidence of UCP2 A55V association with obesity. 20,[22][23][24]26,37,38 Sweeney 39 found heterogeneity of genetic effects by ethnicity on growth and obesity and indicated that genotypephenotype relationships are ethnic specific. Linguistic, archeological and genetic evidence suggests insular populations exist throughout the Pacific region, including Polynesians, Micronesians and Taiwan aborigines.…”
Section: Discussionmentioning
confidence: 99%